Impact of GDP and HDI on Military Expenditures: Survey and Evidence from Dynamic Panel Data Model (Global Journal of Science Frontier Research, 2019)
This study investigates the impact of Gross Domestic Product (GDP) and Human Development Index (HDI) on the Military Expenditures (ME) in 116 countries in the world. First, a rich descriptive statistical analysis is performed for the global time series associated with the GDP and ME for the 116 countries as well as for all the countries in the world. The ratio of ME to GDP has also been analyzed using descriptive statistics. An in-depth graphical analysis is developed by arranging the 116 countries in increasing order from smallest to largest HDI. We classified these 116 countries into four groups according to the four HDI levels. Second, the optimum orders of the DPD model are selected, where all variables are taken in natural logarithm and using the automatic criteria, AIC, BIC, and HQ. By changing the instruments each time, it has been possible to propose the DPD (2, 0, 2) model in first difference form. Third, dealing with the Arellano-Bond (AB) 1-step and 2-step estimators, a study of the determination of valid instruments and the two GMM steps were presented to make the subject more understandable. Finally, the (AB) estimators have been executed, and the findings reveal an immediate positive impact of GDP on military expenditures, while an indirect HDI effect was observed but delayed for two years.
Keywords: Military expenditures; GDP; HDI; dynamic panel data; Arellano-Bond estimator